Skills Improvement for Local Integrated Healthcare Post (Posyandu) Cadres and Housewives through Training on Making Healthy Snacks Based on Fisheries Waste in Benda Baru, South Tangerang - Alitimbul, Mariani; Artanti, Guspri Devi (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
The program aimed at improving the skills of housewives and Posyandu cadres in Benda Baru Village, South Tangerang Regency in the form of training in making healthy snacks based on fishery waste in the form of shrimp shells, which is a community service program aimed at 25 housewives and Posyandu cadres. The expected outcome of the training is an increase in skills as an effort to form / develop a group of people who are economically independent and prosperous. Outputs in community service are snack products from fishery waste, modules for healthy snacks based on fishery waste, scientific publications and publications on activities of making healthy snacks based on fishery waste in the form of a Youtube platform. The method used in this activity is lectures, demonstrations, and practice together with the training participants to make healthy snacks using ingredients from fishery waste in the form of shrimp shells. The results of the training to improve skills in making healthy snacks based on fishery waste were followed well by the participants by making scallops and salted eggs using flour from shrimp shell waste.